Jawabanmu

2014-02-27T20:39:19+07:00
A) Sn = n/2(2a +(n-1)b)
    756=n/2(2.6 + (n-1)3)
     756x2 = n(12+ 3n-3)
     1512=12n+3n2-3n
     1512=3n2+9n
      3n2+9n-1512=0
      n2+3n-504=0
      (n+24) (n-21)=0
       n+24=0 atau n-21=0
        n=-24          n=21(benar karena paositif)
b)Sn=n/2(2a+(n-1)b)
   -36=n/2(2.56+(n-1)-5
   -36x2=n(112-5n+5)
    -72 = n(117-5n)
    -72 = 117n-5n2
    5n2-117n-72=0
    (n-120/5)5(n+3/5)=0
     n-24 =0 atau 5n+3=0
     n=24(benar)  5n=-3
                         n= -3/5
c)Sn=n/2(2a+(n-1)b)
    640=n/2(2.10+(n-1)4
    640=n/2(20+4n-4)
    640=10n+2n2-2n
    640=2n2+8n
    2n2+8n-640=0
     n2+4n-320=0
    (n+20)(n-16)=0
     n+20=0 atau n-16=0
     n=-20           n=16(benar)